1998
DOI: 10.1089/jwh.1998.7.281
|View full text |Cite
|
Sign up to set email alerts
|

Screening Issues in Gynecologic Malignancies for Women with Disabilities: Critical Considerations

Abstract: There are 25 million women with disabilities in the United States. They have biologically similar risks to other women for developing all cancers, including gynecologic malignancies. Unfortunately, barriers to comparable cancer screening include lack of knowledge by women themselves, lack of awareness on the part of health care providers about special health concerns clinicians might encounter, and physical access barriers. Together, these factors conspire to delay diagnosis and treatment of many common gyneco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…One reason could be that the health care providers may have the misconception that women with disabilities are asexual and therefore are at little risk of cervical cancer. 3,4,8,9 Secondly, a Pap smear test requires the patient to lie on an examination table and this could be difficult for some of these disabled women. 4 Furthermore, as many speculate that increasing physician availability may increase the early detection of cancers, 18,20 we examined the relationship between physician availability and routine Pap smear screening.…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be that the health care providers may have the misconception that women with disabilities are asexual and therefore are at little risk of cervical cancer. 3,4,8,9 Secondly, a Pap smear test requires the patient to lie on an examination table and this could be difficult for some of these disabled women. 4 Furthermore, as many speculate that increasing physician availability may increase the early detection of cancers, 18,20 we examined the relationship between physician availability and routine Pap smear screening.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence has shown that women with disabilities diagnosed with early stage breast cancer may have lower rates of breast conserving surgery and higher breast cancer mortality than women without a disability. 7 Although women with a disability share the same risk for breast cancer as women without a disability, 8 they are less likely to obtain a mammogram at recommended screening intervals. [9][10][11] However, these studies examining mammography use among women with a disability use either national data collected in the mid-1990s that is now dated 9,11 or small, not nationally representative samples.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have found disparities in the receipt of preventive services, but results vary with severity of disability and access to physical exams (Diab & Johnston 2004), type of insurance (Sutton & DeJong 1998, Chan et al . 1999), and the gender/disability interface (Thierry 1988, Welner 1998, Iezzoni et al . 2000, Cheng et al .…”
Section: Introductionmentioning
confidence: 99%